THE EMPOWERMENT OF HOUSEWIVES THROUGH THE DEVELOPMENT OF VARIOUS PROCESSED BANANAS IN THE MURUNG RAYA SUB-DISCTRICT: PEMBERDAYAAN IBU RUMAH TANGGA MELALUI PENGEMBANGAN BERBAGAI OLAHAN PISANG DI KELURAHAN MURUNG RAYA - Nurul Hidayah; Maya Rezeki Angriani; Ridha Nur Izzati; Lisa Norsari; Nurhayati (UNUSA Press, 2021)
Based on the survey, it was found that most of the women who manage banana fruit snacks can help to improve the family's economy and make banana chips a superior product in Murung Raya Village, experiencing problems in the management, product, marketing and productivity management areas. The purpose of this activity is to increase knowledge, skills in the field of product management in a safe and healthy manner, online marketing so as to increase family income. . The approach used was community development through training and assistance to economically productive partners, namely the group of women who manage banana processing. The instrument used a check list. The analysis used a descriptive qualitative. The results of the service show that there is an increase in knowledge, skills in product management, packaging, online marketing and an increase in family income. marketing, The community development approach is able to change the knowledge, skills, skills, communication and behavior of partners in managing entrepreneurship effectively and efficiently